Painotettu opetus suomalaiskaupunkien peruskouluverkoissa - Pasu, Terhi; Suomi, Juuso; Siipola, Mari; Koivuhovi, Satu; Seppänen, Piia (Suomen maantieteellinen seura, 2026)
The aim of this study is threefold: to examine pupil selection and grouping into emphasized teaching in comprehensive schools in Finnish cities; to analyze the relationship between pupil selection, pupils’ school journeys, and the socio-economic profiles of pupils’ residential areas; and to examine the geographical placement of emphasized teaching in four of these cities. We combine data from the Community Structure Monitoring System by Statistics Finland and the Finnish Environment Institute, pupil register data of 7th graders (n=8,480) from 2021, and geospatial data on school catchment areas. The results show that while emphasized teaching generally involves permanent grouping, the extent of pupil selection varies. In the four cities examined, emphasized teaching is located in catchment areas with diverse socio-economic characteristics. However, emphasized teaching often serves non-local pupils who face longer school journeys, thus undermining the principle of neighborhood school allocation to varying extents and limiting real choice due to socio-economic and spatial factors.